PERANCANGAN WEBTOON “TRACK RECORD” BAGI REMAJA USIA 13-18 TAHUN SEBAGAI MEDIA TENTANG MENJAUHI KENAKALAN REMAJA DI ERA DIGITAL - Syaharani Dewi, Fanidya; Nirwana, Aditya; Sukmaraga, Ayyub Anshari (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2024)
The transitional period between childhood and adulthood, is a phase brimming with potential yet fraught with challenges. Deviant behaviors or juvenile delinquency are often triggered by a strong desire for acceptance and self-exploration. These actions not only harm oneself, such as hindering academic achievement or damaging social relationships, but also have negative impacts on the surrounding environment. The authors aim to provide teenagers with insights into the causes and consequences of juvenile delinquency conflicts in the digital era. This Webtoon design on juvenile delinquency in the digital era leverages the advancements of technology in accessing digital comics, utilizing the LINE Webtoon platform as the primary medium for accessing the designed story. The authors chose comics as the primary medium due to their appeal and suitability for teenagers. The Webtoon, titled "Track Record," falls under the slice-of-life and drama genres, aligning with everyday conflicts. A qualitative method was employed for this design. Qualitative methods were used to gather data through observations, online interviews, and literature reviews to obtain real-world data on juvenile delinquency in the digital era for the "Track Record" Webtoon story. The result of this Webtoon design is a digital comic in JPG format with a size of 800 x 1280 pixels, uploaded to the LINE Webtoon application. The comic consists of 3 episodes with a minimum of 150 panels per story. The authors also designed supporting media such as tote bags, mugs, tumblers, keychains, and stickers.